Design of Traffic Lights at the Unsignalized Intersection of Narogong Highway-Pangkalan 5 Road Km. 13.5 Bekasi City, West Java - Aulia Choiri; Ribut Nawang Sari; Dinar Ali; Lintang D.A; Yunan Hanun (PT FORMOSA CENDEKIA GLOBAL, 2023)
The intersection of Narogong Highway-Pangkalan road 5, Bantargebang , Bekasi city, is a four-arm intersection that connects Bekasi City with Bogor Regency and is the access to the Bantargebang TPA. The irregular and narrow traffic conditions at the intersection cause frequent traffic jams and are prone to accidents. Therefore, it is necessary to analyze the need for traffic light at the intersection so that a solution can be found in overcoming the problem of congestion and can help smooth the intersection. This analysis is based on the MKJI method (Indonesian Road Capacity Manual) 1997. The results of the analysis show that the intersection of Narogong Highway - Pangkalan road 5, Bekasi City is not able to serve the traffic flow to the maximum, this can be shown by the result of the calculation that has been carried out, so an analysis is needed to improve the performance of the intersection, from the existing calculations alternatives, selected 3 phase alternative with geometric widening, from this solution a cycle time of 80 seconds was obtained with a degree of saturation (DS) = 0.690 to 0.839, and a maximum queue length of 104 meters. The intersection of Jalan Raya Narogong - Jalan Pangkalan 5, Bantargebang , Bekasi City, is intersection four the arm that connects Bekasi City with regency Bogor as well as is access going to to Bantargebang landfill . Condition Then cross that doesn't regular and narrow at intersections the cause often happen congestion and danger happen accident . Therefore _ that is necessary Analysis Need for Traffic Lights at intersections so that obtained solution in overcome problem traffic jams and can help smoothness at intersections . Analysis This based on MKJI method ( Indonesian Road Capacity Manual) 1997. Analysis results is known that , the intersection of Jalan Raya Narogong - Jalan Pangkalan 5 Bekasi City is not capable serve current Then cross with maximum , p This can showed with results calculations that have been made done , so required analysis For increase performance intersection , from alternative existing calculations , selected _ 3 phase alternative with widening geometric , from solution This obtained time cycle by 80 seconds with mark degrees saturation (DS) = 0.690 to 0.839, and long queue maximum 104 meters